Risk factors and mortality of acute kidney injury within 1 month after lung transplantation - Nam Eun Kim (Nature Portfolio, 2021)
Abstract After lung transplantation (LT), some patients are at risk of acute kidney injury (AKI), which is associated with worse outcomes and increased mortality. Previous studies focused on AKI development from 72 h to 1 week within LT, and reported main risk factors for AKI such as intraoperative hypotension, need of ECMO support, ischemia time or longer time on waiting list. However, this period interval rarely reflects medical risk factors probably happen in longer post-operative period. So, in this study we aimed to describe the incidence and risk factor of AKI within post-operative 1 month, which is longer follow up duration. Among 161 patients who underwent LT at Severance hospital in Seoul, Korea from October 2012 to September 2017, 148 patients were retrospectively enrolled. Multivariable logistic regression and Cox proportional hazard models were utilized. Among 148 patients, 59 (39.8%) developed AKI within 1-month after LT. Stage I or II, and stage III AKI were recorded in 26 (17.5%) and 33 (22.2%), respectively. We also classified AKI according to occurrence time, within 1 week as early AKI, from 1 week within 1 month was defined as late AKI. AKI III usually occurred within 7 days after transplantation (early vs. late AKI III, 72.5% vs 21.1%). Risk factor for AKI development was pre-operative anemia, higher units of red blood cells transfused during surgery, colistin intravenous infusion for treating multi drug resistant pathogens were independent risk factors for AKI development. Post-operative bleeding, grade 3 PGD within 72 h, and sepsis were more common complication in the AKI group. Patients with AKI III ([24/33] 72.7%) had significantly higher 1-year mortality than the no-AKI ([18/89] 20.2%), and AKI I or II group ([9/26] 34.6%), log-rank test, P < 0.001). AKI was associated with worse post-operative outcome, 3-month, and 1-year mortality after LT. Severity of AKI was usually determined in early post op period (ex. within 7 days) after LT, so optimal post-operative management as well as recipients selection should be considered.